Twitter and social accountability: Reactions to the Panama Papers. (June 2019) - Neu, Dean; Saxton, Greg; Rahaman, Abu; Everett, Jeffery
Abstract: The potential of social media to disseminate, aggregate, channel and democratize social accountability processes has encouraged a variety of organizations to actively promote and champion such initiatives. These initiatives typically envision a three step social accountability process where, for example, the publication of previously-private financial information about the inappropriate wealth accumulation activities of politicians and their business allies (step #1), combined with social media dissemination and discussion of these activities (step #2), can result in an accountability conversation that spills out of the medium and that sometimes results in positive social change (step #3). The current study examines Twitter reactions to the International Consortium of Investigative Journalist's (ICIJ) publication of the Panama Papers. The analysis illustrates that there was a Twitter reaction: furthermore, that there were different styles of response and that certain styles were more likely to elicit an audience reaction, especially if the tweeter was a journalist or organization. While the provided analysis focuses on step #2 within the social accountability process, the results imply that publicly-interested accounting academics qua activists can facilitate social accountability by helping to make previously-private financial information public and by cultivating sympathetic individuals within the traditional media as well as within organizations that are active on social media.